Enantioselective potential of polysaccharide‐based chiral stationary phases in supercritical fluid chromatography. Issue 6 (24th April 2017) - Kucerova, Gabriela; Kalikova, Kveta; Tesarova, Eva
Abstract: The enantioselective potential of two polysaccharide‐based chiral stationary phases for analysis of chiral structurally diverse biologically active compounds was evaluated in supercritical fluid chromatography using a set of 52 analytes. The chiral selectors immobilized on 2.5 μm silica particles were tris‐(3, 5‐dimethylphenylcarmabate) derivatives of cellulose or amylose. The influence of the polysaccharide backbone, different organic modifiers, and different mobile phase additives on retention and enantioseparation was monitored. Conditions for fast baseline enantioseparation were found for the majority of the compounds. The success rate of baseline and partial enantioseparation with cellulose‐based chiral stationary phase was 51.9% and 15.4%, respectively. Using amylose‐based chiral stationary phase we obtained 76.9% of baseline enantioseparations and 9.6% of partial enantioseparations of the tested compounds. The best results on cellulose‐based chiral stationary phase were achieved particularly with propane‐2‐ol and a mixture of isopropylamine and trifluoroacetic acid as organic modifier and additive to CO2, respectively. Methanol and basic additive isopropylamine were preferred on amylose‐based chiral stationary phase. The complementary enantioselectivity of the cellulose‐ and amylose‐based chiral stationary phases allows separation of the majority of the tested structurally different compounds. Separation systems were found to be directly applicable for analyses of biologically active compounds of interest. Abstract :